Adherence and barriers to Mediterranean diet in Tunisian patients with nonalcoholic fatty liver disease - Ayadi Shema; Trad Nouha; Krifa Nesrine; Mensi Asma; Belhadj Mabrouk Emna; Mouelhi Leila; Dabbeche Radhouene (Future Science OA)
Aim: The burden of non alcoolic fatty liver disease (NAFLD) is globally increasing. While crucial for management, NAFLD patient adherence to the Mediterranean diet (MD) is underexplored, especially in Mediterranean countries such as Tunisia. Materials & methods: A prospective study (Nov 2022–Feb 2023) supervised MD introduction by a nutritionist, evaluated adherence with MEDAS scores (≥10 for good compliance), and explored barriers to good adherence. Results: Among 41 patients (11 male/30 female, mean age 56 [29–70]), 63% had low education and 51% had metabolic syndrome. Good MD adherence stood at 14.6%. Poor adherence tied to diet-induced higher costs (p = 0.021) and difficulty to new-diet adoption (p = 0.026). Conclusion: Tunisian NAFLD patients had low MD adherence due to financial constraints and dietary adaptation challenges.